Tumour model with different imprecise coefficients. Issue 1 (10th September 2021) - Tudu, Suklal; Alam, Shariful
In this paper we have analysed the Bertalanffy tumour model in crisp environment as well as in a fuzzy environment. In fuzzy environment three different types of fuzzy number has been considered for the analysis of the biological tumour model. For all the cases we have taken parametric form of the fuzzy numbers. Numerical examples have also been presented with graphical representation of the solution of the crisp and fuzzy Bertalanffy tumour model.